PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA INSANI TERHADAP KINERJA ISLAMI KARYAWAN PADA PT JAMKRINDO CABANG SURABAYA - Hardityo, Alam Fabian; Fahrullah, Arasy (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of this research is to analyze theinfluenceof training and human resource development withIslamic employee performance ofPT Jamkrindo on Surabayabranch. The author use a quantitive research method with an assosiative approach.Thenumber of samples in   this research are25 respondents. Data collection techniques in this study used a questionnaire and measured with a Likert scale and then processed and with IBM SPSS Statistics 25software. The results of this study indicate that trainingand development, each of which has a significant effect on Islamic employee performance. The training and development variable has a correlation of 81,6%, which means that training and development variable has a positive  contribution of Islamic employee performance and the remaining 18,4% is obtained from other elementnot examined in this study